Efficacy of Dexamethasone Versus Fluticasone Nasal Sprays in Postoperative Patients With Chronic Rhinosinusitis With Nasal Polyps. Issue 5 (September 2019) - Seiberling, Kristin A.; Kidd, Stephanie C.; Kim, Grace H.; Church, Christopher A.
Background: Topical nasal steroids are commonly prescribed to patients with chronic rhinosinusitis with nasal polyposis (CRSwNP) following endoscopic sinus surgery (ESS). They are found to be effective in improving symptoms and quality of life as well as reducing the incidence of nasal polyps recurrence. Objective: We sought to determine whether a higher concentration of topical nasal steroid spray is more effective than the standard nasal steroid spray in controlling symptoms and preventing recurrence of polyps in patients with CRSwNP who underwent ESS. Method: A double-blind randomized controlled trial was performed on patients with CRSwNP after ESS. Patients were randomized into 2 treatment groups: one received topical nasal dexamethasone 0.032% and the other, fluticasone proprionate. The 22-item Sino-Nasal Outcome Test (SNOT-22) and Lund-Kennedy nasal endoscopy scores were measured at the initiation of topical nasal steroid treatment and then at approximately 4-, 8-, and 12-week intervals. Results: Thirty-nine patients were enrolled in the study. Eighteen patients continued using the medications prescribed to them for the duration of the study. There were 8 patients in the dexamethasone group and 10 patients in the fluticasone group. Both groups saw significant improvements in postoperative SNOT-22 and Lund-Kenney scores over time. There was no significant difference in improvement between the groups. Conclusion: There is no significant increased benefit in using a higher dose nasal steroid spray compared to the standard dose nasal steroid spray after ESS.